SEJARAH DALAM KAJIAN STUDI ISLAM: Analisis terhadap Pemikiran Abu Rabi’ - Sudarman Sudarman; Muhammad Hidayaturrahman; Zulfahman Siregar (Program Studi Sejarah Peradaban Islam Fakultas Adab dan Humaniora UIN Imam Bonjol Padang, 2018)
This article examines History in the perspective of Islamic studies, the main study being to analyze the thoughts of Muslim thinkers, Abu Rabi. In his study he revealed that Islam had progressed in various sciences, this happened because Islamic kingdoms encouraged the development of science and technology. The collapse of Islam began when the West carried out colonialism and imperialism. Tension between the West and Islam continues, one way to reconcile these two poles is to dialogue. will indirectly revive an intellectual tradition that is free, dialogical, innovative and creative. This step is considered as an effort to show the teachings of Islam that are compatible with the reality of human life, and not to stay away from it, so that the teachings of Islam are not only in the form of teachings contained in sacred pages.